INNOVATIVE DEVELOPMENT OF THE UKRAINIAN INSURANCE MARKET - Yehorycheva, Svitlana; Taranets , Bogdan (Socio-economic relations in the digital society, 2020)
The content and the features of innovation development of the Ukrainian insurance market are studied. It is confirmed that the historical development of insurance is also a process of innovation, which has significantly accelerated in recent years. The content and the main classification features of insurance innovation are determined. Based on the information of websites and management reports of the insurance companies — leaders of the domestic market, the main trends of their innovation development are identified. It has been proven that the product innovation is the main their type that is implemented. They are associated with improving the consumer quality of insurance products through a combination of risk coverage, customization and digitalization. Car insurance is considered to be the most innovative type of insurance on the Ukrainian market. Insurance companies have responded fairly quickly to the new types of risks related to cyber technologies, the COVID-19 pandemic, and the development of small and medium-sized businesses. Nevertheless they still implement only a limited amount of innovation mainly of incremental and combinatorial types. Insufficient use by insurance companies of modern opportunities to develop communications with customers, as well as the use of information technology to improve internal business processes is indicated. The low level of development of the InsurTech segment in the insurance market of Ukraine, as well as the use of these technologies for innovative development of insurance companies is stated. The results emphasize the need for cooperation between insurance and FinTech companies in the innovation ecosystem, which is still being formed in the Ukrainian insurance market. The role of progressive state regulation to increase the level of innovation of the domestic insurance market is indicated.